Retroalimentación y logros de aprendizaje en ciencias sociales en estudiantes de tercer grado de secundaria de la Institución Educativa N° 6010227 Club De Leones de Lemgo Alemania, San Juan 2025 - Guevara Vásquez, Jhonny (2025)
The study aimed to determine the relationship between feedback and learning achievements in the area of Social Sciences among third-grade secondary students at the Educational Institution No. 6010227 “Club de Leones de Lemgo Alemania,” San Juan (2025). A quantitative approach was adopted, basic in nature, with a descriptive-correlational scope and a non-experimental cross-sectional design. The sample consisted of 105 students; data were collected through an observation guide applied to real classroom situations, paying special attention to how teachers provide guidance, comments, and clear criteria to improve student performance. The results showed a strong positive correlation between feedback and learning achievements (Spearman’s ρ = 0.672; p < 0.001), statistically significant at the 5% level. In practical terms, when feedback is timely, specific, and process-oriented, students demonstrate better performance in Social Sciences. These findings highlight the importance of promoting pedagogical interactions that guide, motivate, and clarify learning goals, providing useful evidence for improving teaching practices and decision-making in school management.